GPER is a mechanoregulator of pancreatic stellate cells and the tumor microenvironment. (11th December 2018) - Cortes, Ernesto; Sarper, Muge; Robinson, Benjamin; Lachowski, Dariusz; Chronopoulos, Antonios; Thorpe, Stephen D; Lee, David A; del Río Hernández, Armando E
Abstract: The mechanical properties of the tumor microenvironment are emerging as attractive targets for the development of therapies. Tamoxifen, an agonist of the G protein‐coupled estrogen receptor (GPER), is widely used to treat estrogen‐positive breast cancer. Here, we show that tamoxifen mechanically reprograms the tumor microenvironment through a newly identified GPER‐mediated mechanism. Tamoxifen inhibits the myofibroblastic differentiation of pancreatic stellate cells (PSCs) in the tumor microenvironment of pancreatic cancer in an acto‐myosin‐dependent manner via RhoA‐mediated contractility, YAP deactivation, and GPER signaling. This hampers the ability of PSCs to remodel the extracellular matrix and to promote cancer cell invasion. Tamoxifen also reduces the recruitment and polarization to the M2 phenotype of tumor‐associated macrophages. Our results highlight GPER as a mechanical regulator of the tumor microenvironment that targets the three hallmarks of pancreatic cancer: desmoplasia, inflammation, and immune suppression. The well‐established safety of tamoxifen in clinics may offer the possibility to redirect the singular focus of tamoxifen on the cancer cells to the greater tumor microenvironment and lead a new strategy of drug repurposing. Synopsis: GPER agonist tamoxifen reprograms pancreatic stellate cells versus a non‐myofibroblastic phenotype, reducing their ability to remodel the ECM in PDAC. The resulting tumor microenvironment is less conducive to cancer cell invasion, macrophage recruitment and M2‐polarization. GPER regulates myofibroblastic differentiation in pancreatic stellate cells. Tamoxifen inhibits ECM remodelling by pancreatic stellate cells to suppress cancer cell invasion. The GPER‐RhoA‐MLC‐2‐axis controls YAP activation. Tamoxifen modulates desmoplasia, inflammation and immune response in pancreatic cancer. Abstract : GPER agonist tamoxifen reprograms pancreatic stellate cells versus a non‐myofibroblastic phenotype, reducing their ability to remodel the ECM in PDAC. The resulting tumor microenvironment is less conducive to cancer cell invasion, macrophage recruitment and M2‐polarization.